2006
DOI: 10.1007/s00210-006-0091-0
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase II beta expression level correlates with doxorubicin-induced apoptosis in peripheral blood cells

Abstract: Anthracyclines are widely used in oncology. Both the response and side-effects of anthracyclines are individually variable, but determinants or predictive markers of this variability are not available. We investigated the variability in the expression of the anthracycline targets topoisomerases II (topo II) alpha and beta and its significance for the apoptotic response following exposure to the anthracycline doxorubicin. Only topo II beta protein expression was detected in peripheral blood cells. Usually consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
2
17
0
2
Order By: Relevance
“…TOP2B expression is correlated with cellular sensitivity to doxorubicin [31] and the TOP2B protein is necessary for development of anthracycline-induced cardiotoxicity in mice [13]. Using bioinformatics tools we identified a SNP (rs2363520) that is highly associated with TOP2B expression (p = 9 × 10 -6 ) in lymphoblastoid cell lines [32].…”
Section: Resultsmentioning
confidence: 99%
“…TOP2B expression is correlated with cellular sensitivity to doxorubicin [31] and the TOP2B protein is necessary for development of anthracycline-induced cardiotoxicity in mice [13]. Using bioinformatics tools we identified a SNP (rs2363520) that is highly associated with TOP2B expression (p = 9 × 10 -6 ) in lymphoblastoid cell lines [32].…”
Section: Resultsmentioning
confidence: 99%
“…These results support the critical concept that doxorubicin-induced cardiotoxicity is mediated by Top2β in cardiomyocytes. 39 (Figure 1)…”
Section: Novel Mechanisms Of Anthracycline Cardiotoxicity Are Identifiedmentioning
confidence: 99%
“…It has been reported that Top2β levels in peripheral blood are correlated with the apoptotic response of leukocytes to doxorubicin in humans. 39 Hence, the Top2β level in peripheral blood may be useful as a surrogate marker for susceptibility to anthracycline-induced cardiomyopathy. However, this remains to be proven in clinical studies.…”
Section: Novel Mechanisms Of Anthracycline Cardiotoxicity Are Identifiedmentioning
confidence: 99%
“…top2a expression is elevated in solid tumors and predicts responsiveness to anthracycline-based chemotherapy in women with primary breast cancer (33,183,226). Similarly, top2b levels in hematological cells correlates with sensitivity to and apoptosis by doxorubicin (117). The relationship between top2a and top2b and drug sensitivity in cancer is complex due to the role of the drug resistance proteins p-glycoprotein and multidrug resistance protein, changes in subcellular localization of top2 proteins, shared homology and catalytic activity between top2a and top2b, and phosphorylation/mutations in top2 (185).…”
Section: Raomentioning
confidence: 99%